Distribution and transformation of dissolved organic matters (DOMs) in membrane distillation for desulfurization wastewater in thermal power plant. (April 2022) - Zheng, Libing; Zhang, Chun; Wang, Jun; Yu, Dawei; Zhong, Hui; Hou, Deyin; Wei, Yuansong
Abstract: The organic fouling mechanism and its control are patchy in membrane distillation (MD) process, as the distribution and transformation of dissolved organic matters (DOMs) in MD are poorly understood due to its application scenarios for high salinity wastewater. In this work, MD performance for desulfurization wastewater was evaluated over a 65 d long-term operation, with a focus on the composition, distribution, and transformation of DOMs. MD shows good tolerance to the high concentrations of salts and DOMs (salt rejection > 99%, organic matter rejection > 98%), with high flux of 15 kg/m 2 ·h and high flux recovery as Fr was 99.7%. Polyaromatic hydrocarbon (PAHs), tryptophan- or protein-like, and autochthonous-sourced humic acids (FI was around 2) were main DOMs in feedwaters, and the spatio-temporal distribution and transformation appeared result from the membrane interception and microbial processes. Tryptophan/ tyrosine increased in the feedwaters, and becoming the dominant permeate component as the operation time prolonged. While proteins and PAHs also penetrated as the membrane was progressively wetted. Proteins was easily peeled off form membrane surface during cleaning, followed by PAHs, while tryptophan/tyrosine were protected by the biofilm. It demonstrating the vertical distribution of DOMs on foulants layer, which need further attention for membrane fouling control. This study demonstrates the potential of MD in desulfurization wastewater treatment and offers a new insight into the DOMs distribution and transformation, which could deepen the understanding of the organic fouling mechanism in MD. Graphical abstract: Unlabelled Image Highlights: MD showed promising potential for desulfurization wastewater treatment. Tryptophan/tyrosine, protein, and PAH were identified in MD by 3DEEM-PARAFAC. Spatial and vertical distribution of DOM in MD and foulants layer were revealed. Membrane interception and microbes contribute to the DOM distribution and transformation. Proteins was easily peeled by cleaning, tryptophan/tyrosine were more stubborn.